Chemical communication in the reproduction of the peacock blenny, Salaria pavo (Pisces: Blenniidae) - Serrano, Rui M. (2009)
The peacock blenny Salaria pavo (Risso, 1810) is a small bottom-living teleost found in the littoral zone of the Mediterranean sea and adjacent Atlantic coast. Males occupy holes or crevices in rocks where females come to spawn and the males subsequently guard the eggs. Males develop anal glands from the epidermis of the first two rays of the anal fin concurrent with development of the gonads. It has previously been shown that this gland is the source of putative sex pheromones that attract females in reproductive condition. Males also possess accessory reproductive organs (testicular glands and blind pouches) which may also produce sex pheromones. This study aimed to test whether male S. pavo have evolved a specialization in the way they produce and release pheromonal signal(s), providing an example where true chemical communication has evolved in fish. Four experimental chapters attempt to answer specific questions. The main results and conclusions of the experiments are summarized as follows. Behavioural and olfactory responses of female Salaria pavo (Pisces: Blenniidae) to putative pheromones from the anal gland of males A pair of anal glands on the anal fin of male Salaria pavo is suggested to be a specialised structure for the production/release of (a) putative sex pheromone(s) that attracts females and affects their mate choice. However, it is not known whether female reproductive condition affects their response to the putative pheromone. Furthermore, the chemical nature of this putative pheromone is unknown. In a flow-through tank or fluviarium, video-tracking locomotion analysis showed that, during the first up-current trajectory in the test area, reproductive females were attracted to water conditioned by males with anal glands but not to water conditioned by the same males after anal gland excision. During the entire observation (5 min), however, the females were attracted to water conditioned by males with, and without, anal glands. Anal gland macerate attracted reproductive females during the first up-current trajectory but did not attract non-reproductive females; reproductive and non-reproductive females were not attracted to the macerate during the entire observation. Using electro-olfactogram recordings in females, we investigated the olfactory potency of: (1) macerate and solid-phase extraction (SPE) fractions of fully developed anal glands; (2) SPE eluates of maleconditioned water before and after excision of partially and fully developed anal glands, and fractions obtained by reverse-phase high-performance liquid chromatography; and (3) molecular-weight fractions of macerated fully developed anal glands. Undifferentiated anal fin-rays and skin macerates were used as control. Altogether, the results suggest that fully developed anal glands secrete hydrophilic odorants comprising mostly molecules smaller than 500 Da but also molecules larger than 10 kDa. In addition, males release to the water less hydrophilic odorants that do not originate from the anal glands. Our study suggests that fully developed anal glands produce and release water-soluble substances acting as putative pheromones for attraction of reproductive females. Since odorants not originating in the anal glands may also contribute to female attraction, we suggest that chemical attraction of females to potential mates involves a multi-component odour comprising the anal gland pheromone plus other odorants. Seasonal cell differentiation promotes odorant secretion in the anal gland of male Salaria pavo (Pisces: Blenniidae) Male Salaria pavo develop anal glands from the epidermis of the first two rays of the anal fin concurrent with development of the gonads. The putative pheromone(s) produced and/or released are olfactory detected and attractive to reproductive females. We investigated the morphologic and cellular characterization of the anal gland during the annual reproductive cycle by histochemistry and electron microscopy, and the odorant secretion by electro-olfactogram (EOG) recording in conspecific females. The anal gland is a highly folded glandular epithelium which contains cells that undergo cyclic differentiation into clusters of secretory cells during the breeding season and then degenerate. Secretory cells produce neutral mucins and neighbour mucous cells produce acidic mucins. The presence of these cells was correlated with olfactory activity; EOG recordings showed that fully developed anal gland secretions, in which secretory cells are present, elicited significantly greater olfactory responses than those of partially developed anal glands, in which the secretory cells are absent. These results suggest that anal gland cell differentiation is responsible for odorant secretion, which could act as sex pheromones. 11-ketotestosterone stimulates anal gland differentiation and pheromone secretion in the peacock blenny, Salaria pavo (Pisces: Blenniidae) The anal gland of male Salaria pavo undergoes seasonal cell differentiation and produces pheromones that attract reproductive females. This study investigated the effect(s) of the steroid 11-ketotestosterone (KT), a potent androgen, on anal gland cell differentiation and function. Silastic tubes containing castor oil (control) or KT (5 mg.kg-1) in castor oil (KT-treated) were implanted in the peritoneal cavity of males. The area of the anal gland was measured weekly. After three weeks, the effect on anal gland cell differentiation was investigated by histochemistry and electron microscopy. The anal glands were incubated in vitro for 24 hours and the olfactory potency of the incubation medium was assessed by electro-olfactogram recording in conspecific females. The anal gland of KT-treated males grew significantly faster than that of controls during the first week. After seven days, characteristic clusters of secretory cells appeared in the anal gland epithelium of all KT-treated males but not in those of controls. Culture medium of anal glands of KT-treated males elicited greater olfactory responses than those from controls. This increase was correlated with the percentage of secretory cells in the anal gland. This study shows that KT stimulates both development and functional structure of the anal gland, promoting putative sex pheromone production. 11-ketotestosterone stimulates accessory reproductive organs and possible pheromone secretion in the peacock blenny, Salaria pavo (Pisces: Blenniidae) This study investigated the effect(s) of the androgen 11-ketotestosterone (KT) on the development of testes, testicular glands and blind pouches, and the secretion of possible sex pheromones in Salaria pavo males. Silastic tubes containing castor oil (control) or KT (5 mg.kg-1) in castor oil (KT-treated) were implanted in the peritoneal cavity. After three weeks, the effect on testis and testicular gland cell differentiation was investigated using histochemistry. The testes plus the testicular glands (testicular tissue) were incubated in vitro for 24 hours. The olfactory potency of the testicular tissue culture medium, and the fluids of the blind pouches and gall bladder, was assessed by electro-olfactogram recording in conspecific females. KT-treated males had larger gonadossomatic index than controls due larger testicular glands; KT stimulated testicular gland growth and sialomucin secretion, but had no effect on the testis. Culture medium of testicular tissue, blind pouch and bile fluids from KT-treated males elicited greater olfactory responses than those from controls. Thus, KT stimulates the development of the testicular gland and blind pouches and promotes odorants production. Together, these odorants could form part of a pheromonal 'bouquet', the production of which is stimulated by KT. Conclusions 1. The anal gland produces and releases putative sex pheromones which attract conspecific reproductive, but not non-reproductive, females. 2. The anal gland produces and releases several water-soluble substances during the breeding season that are detected by the olfactory system of conspecific females. 3. The differentiation of secretory cells in the anal gland during the breeding season seems to be responsible for secretion of odorants which, in turn, act as putative pheromones. 4. The putative sex pheromones from the anal gland are different in chemical nature from those derived from sexual hormones (such as steroids and prostaglandins). Amino acids, peptides and glycoproteins are all candidates. 5. KT stimulates the anal gland development, which is associated with increased putative sex pheromone secretion. 6. KT also stimulates development of the testicular gland and blind pouch which, in turn, may also produce sex pheromones. It is conceivable that these putative sex pheromones are hormone derivatives. This study suggests that male S. pavo produce chemical signals, releasing odorants not only from the anal gland, but also from the testicular glands and blind pouches. These odours could constitute a pheromonal “bouquet”, which is released by parental males to attract reproductive females. The chemical identity of these pheromonal compounds remains unknown. However, this “bouquet” may include hormonal metabolites which could act as hormonal pheromones (as seen in other teleosts) and specific compounds produced by the anal gland which are important in the attraction of reproductive females. This study provides strong evidence that S. pavo has evolved specialization of pheromone production. This species, and probably other blennids, is therefore an example of true chemical communication in fish; such specialization may be due to their particular behavioural ecology and mating strategy, where sexual selection has been an important factor in its evolution.